Poisson structures on cotangent bundles - Gabriel Mitric (International Journal of Mathematics and Mathematical Sciences)
We make a study of Poisson structures of T∗M which are graded structures when restricted to the fiberwise polynomial algebra and we give examples. A class of more general graded bivector fields which induce a given Poisson structure w on the base manifold M is constructed. In particular, the horizontal lifting of a Poisson structure from M to T∗M via connections gives such bivector fields and we discuss the conditions for these lifts to be Poisson bivector fields and their compatibility with the canonical Poisson structure on T∗M. Finally, for a 2-form ω on a Riemannian manifold, we study the conditions for some associated 2-forms of ω on T∗M to define Poisson structures on cotangent bundles.